Computational Ghost Imaging with Multiplexed Time-Varying Signals. (18th July 2020) - Qiu, Panghe; Ye, Zhiyuan; Bai, Zhichen; Liu, Xin; Bo, Su
Abstract : This study proposes two methods of optical watermarking based on multiplexed time-varying signals for computational ghost imaging using the Hadamard matrices. The proposed methods can realize image fusion and dual optical encryption. The time-varying signal is encoded into a specific Hadamard coefficient in advance and hidden in the light source of the transmitting end as a multiplicative factor or loaded at the receiving end as an additive factor. Theory and experiments confirm the feasibility of this scheme. Moreover, the scheme is highly scalable and has potential applications in multispectral single-pixel imaging.